If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13m = 12m + -21 Reorder the terms: 13m = -21 + 12m Solving 13m = -21 + 12m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12m' to each side of the equation. 13m + -12m = -21 + 12m + -12m Combine like terms: 13m + -12m = 1m 1m = -21 + 12m + -12m Combine like terms: 12m + -12m = 0 1m = -21 + 0 1m = -21 Divide each side by '1'. m = -21 Simplifying m = -21
| x*2*x^3*x^5= | | (2z+6)(2z-6)z= | | 13/11y-2/11y=-3 | | -2(b-4)=2b+8 | | -5(7x-12)+2(-6-10x)=-10x+3x | | (-2y^2)(4y)= | | z^2+3=4z | | -15x-1/3= | | z^2+3=3z | | q^2+19=20q | | 6x-3=4x+13 | | k/5.2+81.9=47.2 | | 14.5+x=6.2 | | x+15=-34 | | 4x^2-7=71 | | 2a^-1+3b^-2/a^-1-b^-1 | | x^4+14x^2+49= | | x^4-14x^2+49= | | (9x+7)(4x^2+5x+8)= | | -11(8p+4)=-11(p+11) | | -3x+2(-4)=10 | | 35p^6q^3/49p^6q^2 | | X+1/3x=36 | | 30/14=m/1.54 | | x^2+2x=26.01 | | 4(3x-4)=2(x-2) | | 9x-4=2(x+3) | | 3(5x-6)=-48 | | 4/3v-4/3 | | 26x+144x=0 | | 1/24*65^2=150 | | 14x-25x=9x |